The COVID-19 Pandemic. A Psychosocial Approach in Mexican Medical Students - Diego Ortega-Moreno; Edgar Botello-Hernández; Rebeca Aguayo-Samaniego; Patricio García-Espinosa (University Library System, University of Pittsburgh, 2022)
Background: Nowadays the impact that the COVID-19 pandemic has had on students around the world is not a secret; the loss of the status quo as a consequence of the SARS-CoV-2 infection, changed the concept of everyday life. Medical students represent an important affected population in terms of loss of theorical, laboratory practices, as well as the much-needed exposure to patients, are factors that add to the baseline stress of being a college student and alienation from social groups. The present study sought to establish the impact on the emotional and social spheres of medical students, in addition to establishing risk factors, predictors or predisposing factors to present alterations in in the psychosocial elements of health. Methods Cross-sectional study performed in Mexican Medical Students; the sample size was found to be 366. An 82-item questionnaire was applied to assess 4 main axes; Generalized Anxiety Disorder (GAD-7) and the Patient Health Questionnaire (PHQ-9) were used to evaluate prevalence of anxiety and depression, COVID-19 knowledge, perception, and social determinants were also evaluated. The study sample was divided into 2 groups to address a group with depression/anxiety and a group with no anxiety/depression. The possible presence of anxiety/depression was defined as a score ≥10 on both scales. 500 students were randomly chosen, were invited to participate, and voluntarily signing the informed consent. Students who did not complete all answers were excluded. Non-parametric quantitative variables were evaluated with Mann-Whitney U, qualitative variables with χ2 or Fisher's exact test. Spearman's correlation was also used, and a binary logistic regression was done to identify association. Results A total of 384 students were included with a mean age of 21 years. The majority, 236 students, were women (61.45%) and 154 (40.1%) belonged to the clinical semesters of the career (7th to 12th semester). 89.34% (343 students) stated that their main concern was that a family member became ill, the economy (71.51%), and massive reinfection (68.44%). A moderate to exaggerated increase in anxiety symptomatology before the start of the pandemic was reported in 61.19% (235 students), 75% (287 students) reported depressed mood symptoms. 320 students (83.33%) reported having been correctly informed; they were aware of COVID-19 symptomatology, use of protective personal equipment, and myths. We found that 43% (PHQ-) had depression and 24.5% anxiety (GAD-7); having depression increased the risk of presenting anxiety and vice-versa along with identifying themselves as a woman and having a diagnosis of a prior psychiatric disorder for both groups. Belonging to clinical semesters was found to be as a protective factor for both anxiety and depression. Conclusion The results indicate an increase in the depressive and anxiety symptomatology of the students, as well as concerns for their families and the economic situation. Academic institutions must design effective strategies for early detection, treatment and increase resilience of students using innovative resources adapted to the contingency.